Do Education Investment and Welfare of Labor Affect Productivity Growth in Indonesia? - Rizqon Halal Syah Aji; Roziana Baharin; Ishak Yussof; Mohd Nasir bin Mohd Saukani (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Increasing the education budget in Indonesia has become the focus of economic politics because it is a fundamental issue. Education, as a significant component of labor productivity, plays a vital role in driving the welfare of the workforce due to the increase in the Total Factor Productivity (TFP). This paper aims to test the quality of tertiary education by using World Bank and APO data. This paper provides an overview of tertiary education that influences TFP when juxtaposed with several other control variables and uses the ARDL (Autoregressive Distributed Lag) test. The results show that TFP growth is significantly positively affected by the improvement of tertiary education quality and production capital but is significantly affected by the welfare of the workforce. This study implies that the government must allocate an adequate budget to improve education quality in Indonesia.How to Cite:Aji, R. H. S., Baharin, R., Yussof, I., & Mohd Saukani, M. N. (2022). Do Education Investment and Welfare of Labor Affect Productivity Growth in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 273-288. https://doi.org/10.15408/sjie.v11i2.26401.